Chlamydial proctitis? - Munday, P E (1985)
Chlamydia trachomatis was isolated from 21 (7%) of 309 specimens obtained in October 1982 from the rectum of homosexual men undergoing proctoscopy. During the same period Neisseria gonorrhoeae was isolated from 12 (3%) of 454 specimens obtained similarly. The clinical features of patients infected with each of these micro-organisms were compared with those of an uninfected group of homosexual men. No characteristic diagnostic features were noted in the infected men.